বাংলাদেশে গৃহকর্মী নির্যাতন: প্রচলিত ও ইসলামী আইনে এর প্রতিকার ব্যবস্থা | Violence against Domestic Workers in Bangladesh: It’s Remedy in Conventional and Islamic Law (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
Domestic work is one of the oldest professions in the world. A great number of employees ranging from 52.6 to 100 million is engaged in domestic works across the globe. Though such great number of people invests their labours in domestic works inside home, they are still victimized by their persecuting masters. Since the inception of civilization, violence against domestic workers is an antique social phenomenon. In the modern consumerist society it has become a pestilence. Though various laws are promulgated and executed, it cannot be controlled as per expectation. To control this indoor crime, an integrated and harmonized system of both conventional and Islamic law is needed. To conduct an extensive research based on both the legal norms is painstakingly required which would offer an effective legal mechanism and thereby this crime would be stopped and removed from the society. The article is a humble initiative to achieve that goal. Qualitative and descriptive methods have been employed to conduct this research. In this article violence against domestic workers has been introduced and various aspects of such violence coupled with a survey-based feature, has been depicted. In addition to this, the loopholes of existing laws have been addressed. Besides this, the highly sophisticated and benevolent humanitarian attitude of Islam towards domestic workers has been demonstrated.সারসংক্ষেপ: গৃহকর্ম পৃথিবীর পুরনো পেশাসমূহের একটি। বর্তমান বিশ্বে প্রায় ৫২.৬ থেকে ১০০ মিলিয়ন মানুষ গৃহ শ্রমে নিয়োজিত রয়েছে। এই বিশাল জনগোষ্ঠী গৃহাভ্যন্তরে তাদের শ্রম বিনিয়োগ করে। তাদের অনেকেই গৃহকর্তা কর্তৃক নির্যাতনের শিকার হয়। গৃহকর্মী নির্যাতন অতি পুরনো সামাজিক ইস্যু হলেও বর্তমানে তা ভয়াবহ আকার ধারন করেছে। প্রচলিত নানা আইন দিয়েও কাক্সিক্ষত মাত্রায় এর প্রতিরোধ সম্ভব হচ্ছে না। গৃহাভ্যন্তরে ঘটতে থাকা এ অপরাধের লাগাম টেনে ধরার জন্য প্রচলিত ও ইসলামী আইনের আলোকে একটি সমন্বিত ব্যবস্থার প্রয়োজন। উভয় ধারার আইনকে সামনে রেখে গৃহকর্মী নির্যাতন প্রতিরোধে কার্যকর আইনী রূপরেখা প্রণয়নের স্বার্থে ব্যাপক গবেষণা আবশ্যক। আলোচ্য প্রবন্ধটি এ লক্ষ্য অর্জনের পথে একটি ক্ষুদ্র প্রয়াস। এ গবেষণায় গুণাত্মক বর্ণনামূলক পদ্ধতি অনুসরণ করা হয়েছে এবং গৃহকর্মী নির্যাতনের পরিচয়, ধরন ও পরিসংখ্যানভিত্তিক চিত্র তুলে ধরার পাশাপাশি এটি প্রতিরোধে প্রচলিত আইনের দুর্বলতাগুলোর প্রতিও ইংগিত করা হয়েছে। তাছাড়া গৃহকর্মীদের ব্যাপারে ইসলামের উদারনৈতিক ও উন্নত মানবিক দৃষ্টিভঙ্গি এতে প্রতিভাত হয়েছে।